Human-Wild Animals Conflict in and around Amba Forest, Ezha District, Gurage Zone, Southern Ethiopia - Sime, Demelash; Siraj, Zemedkun; Teklemariam, Ashenafi; Tilahun, Belete (International Journal of Zoology, 2022)
The conflicts between humans and wild animals with the same resources are common but seldom reported in Ethiopia. This study was carried out to assess the causes, impacts, and mitigation strategies of the local communities with human-wild animal conflict (HWC) in and around Amba forest of Ezha District, Gurage Zone, Ethiopia: implications for wildlife conservation. Cross-sectional study design was applied, and data were collected from November 2019 to July 2020 through a semistructured questionnaire, focus group discussion (FGD), and field observation. A total of 53 respondents were randomly selected. The data were analyzed using SPSS software, and the results were presented using tables, graphs, charts, and text. The study result revealed that human-wild animal conflict exists, and it was seriously occurring at various places, time, and seasons. Papio anubis, Potamochoerus larvatus, Cercopithecus aethiops, Hystrix cristata, and Crocuta crocuta were the main conflicting wild animals, respectively. Abundance of wild animals, presence of forest, crop raiding, expansion of agriculture, and livestock predation were the main causes of conflict in the study area. There was a statistically significant relation between conflict and the cause of conflict (χ2(5) = 17.075, p=0.004). Psychological and economic impacts were the main impacts encountered. Most of the respondents (86.8%) had applied conflict mitigation strategies, but it was ineffective, although the trend of conflict was increasing. Many of the respondents (41.5%) had a negative attitude toward wild animals, but 58.5% encouraged wild animals’ conservation. HWC had increasing trends of conflict, and thus, a negative attitude was developed by the communities on wild animal coexistence and conservation. Therefore, awareness creation, training, and promoting coexistence mechanisms between humans and wild animals are necessary in the study area.